363OTreatment with pralsetinib (formerly BLU-667), a potent and selective RET inhibitor, provides rapid clearance of ctDNA in patients with RET-altered non-small cell lung cancer (NSCLC) and medullary thyroid cancer (MTC). (24th November 2019) - Lee, D H; Subbiah, V; Gainor, J F; Taylor, M H; Zhu, V W; Doebele, R C; Lopes, G; Baik, C; Garralda, E; Gadgeel, S M; Kim, D-W; Turner, C D; et al.
Abstract: Background: Pralsetinib, an investigational agent, is a potent and selective inhibitor of oncogenic rearranged during transfection (RET) alterations and predicted resistance mutations. Up to 90% of advanced MTC is characterized by single nucleotide variants and short insertions/deletions in the RET gene. In NSCLC, 1–2% of patients (pts) harbor rearrangements resulting in RET fusions. In the first-in-human ARROW study (NCT03037385), pralsetinib showed significant clinical activity in RET-altered NSCLC and MTC and was well tolerated. Previous data show that early decline in circulating tumor DNA (ctDNA) may predict treatment outcome. We investigated the change in ctDNA levels from baseline following treatment with pralsetinib and whether early changes in ctDNA during treatment were associated with clinical responses and outcomes. Methods: Blood was collected at baseline and prespecified time points during treatment. Plasma from 111 pts with locally documented RET-altered MTC and NSCLC were profiled with the Personal Genome Diagnostics PlasmaSELECT™ R64 sequencing panel. Results: RET fusions were detected at baseline in 45/63 (71%) of pts with NSCLC and RET mutations in 35/48 (73%) of pts with MTC. Baseline ctDNA mutant allele fraction ?MAF; MTC? or unique fusion reads (NSCLC) correlated with the sum of target lesions ?P<0.01?. Pralsetinib led to rapid RET ctDNA decline in almost all pts and across all doses (60–600 mg QD, 100–200 mg BID). Eighty-one percent of pts with NSCLC and detectable ctDNA at baseline had undetectable RET ctDNA after 8 weeks of treatment. Clearance of RET fusions in NSCLC was observed for multiple fusion partners including CCDC6 and KIF5B. ctDNA was also undetectable after 8 weeks in 41% of pts with MTC harboring somatic RET mutations. The correlation between change in ctDNA level and clinical outcome is not yet mature, but will be reported. Conclusions: Treatment with pralsetinib led to a robust and rapid decline in ctDNA in almost all patients regardless of treatment dose or tumor diagnosis and in NSCLC irrespective of fusion partner studied. Clinical trial identification: NCT03037385. Editorial acknowledgement: Third-party writing assistance was provided by Meredith Kalish, MD, of Ashfield Healthcare Communications, part of UDG Healthcare plc, and funded by Blueprint Medicines Corporation. Legal entity responsible for the study: Blueprint Medicines Corporation. Funding: Blueprint Medicines Corporation. Disclosure: D.H. Lee: Honoraria (institution): AstraZeneca; Honoraria (institution): Boehringer Ingelheim; Honoraria (institution): Bristol-Myers Squibb; Honoraria (institution): CJ Healthcare; Honoraria (institution): Eli Lilly; Honoraria (institution): Janssen; Honoraria (institution): Merck; Honoraria (institution): MSD; Honoraria (institution): Mundipharma; Honoraria (institution): Novartis; Honoraria (institution): Ono; Honoraria (institution): Pfizer; Honoraria (institution): Roche; Honoraria (institution): Samyang Biopharm; Honoraria (institution): ST Cube; Advisory / Consultancy: Ministry of Food and Drug Safety, Korea; Advisory / Consultancy: Health Insurance Review and Assessment Service, Korea; Advisory / Consultancy: National Evidence-based Collaborating Agency, Korea; Advisory / Consultancy: National Cancer Control Planning Board, Korea. V. Subbiah: Advisory / Consultancy: MedImmune; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): NanoCarrier; Research grant / Funding (institution): Northwest Biotherapeutics; Research grant / Funding (institution): Genentech/Roche; Research grant / Funding (institution): Berg Pharma; Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer AG; Research grant / Funding (institution): Incyte; Research grant / Funding (institution): Fujifilm; Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar; Research grant / Funding (institution): D3 Oncology Solutions; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Multivir; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution): Loxo Oncology; Research grant / Funding (institution): Vegenics; Research grant / Funding (institution), Takeda, Alfasigma, Sgensys, Idera, Boston Biomedical, Inhibrx, Exelixis: Remainder of organizations here due to space constraints. J.F. Gainor: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Merck; Honoraria (self): Incyte; Honoraria (self), Research grant / Funding (institution): ARIAD Pharmaceuticals; Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self): Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Genentech; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Theravance; Advisory / Consultancy: Loxo; Advisory / Consultancy: Takeda; Advisory / Consultancy, Research grant / Funding (institution): Array BioPharma; Advisory / Consultancy: Amgen; Advisory / Consultancy: Agios; Advisory / Consultancy: Regeneron; Advisory / Consultancy: Oncorus; Advisory / Consultancy, Research grant / Funding (institution): Jounce Therapeutics; Research grant / Funding (institution): Adaptimmune; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution), Moderna Therapeutics, Tesaro, Alexo Therapeutics: Remainder of organizations due to space constraints. M.H. Taylor: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: BMS; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Eisai Inc; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Array Biopharma; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Loxo; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Blueprint; Honoraria (self), Advisory / Consultancy: Arqule; Honoraria (self), Advisory / Consultancy: Novartis; Research grant / Funding (institution): BioAtla. V.W. Zhu: Honoraria (self), Speaker Bureau / Expert testimony: AstraZeneca; Honoraria (self), Speaker Bureau / Expert testimony: Roche-Foundation Medicine; Honoraria (self), Speaker Bureau / Expert testimony: Roche/Genentech; Honoraria (self), Speaker Bureau / Expert testimony: Takeda; Advisory / Consultancy, Shareholder / Stockholder / Stock options: TP Therapeutics. R.C. Doebele: Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: ARIAD Pharmaceuticals; Honoraria (self), Travel / Accommodation / Expenses: Guardant Health; Honoraria (self): Takeda Pharmaceuticals; Honoraria (self): Spectrum Pharmaceuticals; Honoraria (self), Advisory / Consultancy: Trovagene; Advisory / Consultancy: OncoMed Pharmaceuticals; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses, Licensing / Royalties, Licensing fees to institution for biologic materials: Ignyta; Advisory / Consultancy: GreenPeptide; Shareholder / Stockholder / Stock options: Rain Therapeutics; Licensing / Royalties, licensing fees for patent PCT/US2013/057495: Abbott Molecular. G. Lopes: Advisory / Consultancy: Pfizer; Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Merck Sharp & Dohme; Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution): Tesaro; Research grant / Funding (institution): Bavarian Nordic; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): G1 Therapeutics. E. Garralda: Research grant / Funding (self), Research grant / Funding (institution): Novartis; Travel / Accommodation / Expenses: BMS; Travel / Accommodation / Expenses: Menarini; Travel / Accommodation / Expenses: Glycotope; Licensing / Royalties: MSD. S.M. Gadgeel: Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Genentech; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: ARIAD Pharmaceuticals; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: AbbVie; Research grant / Funding (self), Research grant / Funding (institution): Merck; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution), Travel / Accommodation / Expenses: Takeda. C.D. Turner: Full / Part-time employment: Blueprint Medicines. M. Palmer: Full / Part-time employment: Blueprint Medicines. S. Miller: Full / Part-time employment: Blueprint Medicines. G. Curigliano: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Seattle Genetics; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Lilly; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: BMS; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer. All other authors have declared no conflicts of interest.